The Effect of British Accent Movie in Increasing Speaking Skills at SMA Muhammadiyah Sungguminasa - Nurismi; ul Haq, Muhammad Zia; Sastrawati, Ika (Journal of Computer Interaction in Education, 2020)
This study aims to determine the improvement of students' speaking skills by using British Movies as a medium to improve students' speaking skills in terms of pronunciation. This study uses pre-experimental research with one class pre-test and post-test. The researcher used a purposive sampling technique. The sample of this study was the science students of SMA Muhammadiyah Sungguminasa for the academic year 2021/2022, totaling 8 students. The researcher used pictures as an instrument in the Pre-test and Post-test.students' pronunciation issues when speaking can be minimized using English films as evidenced by the results found, that the main score of students' pronunciation is 0.15 which is bad, the post-test 0.23 is sufficient and the increase from pre-test to post-test is 49, %.The results of the increase are also proven by the value of the t-test. The researcher found that the t-test was lower than the t-table, pronunciation (1.87 < 1.891). it means that there is no significant increase, but there is an increase of about 49%. In other words, the use of British Movies can improve students' speaking skills in terms of pronunciation in Class XI SMA Muhammadiyah Sungguminasa.